2008
DOI: 10.1002/hbm.20588
|View full text |Cite
|
Sign up to set email alerts
|

A voxel‐based morphometry study of frontal gray matter correlates of impulsivity

Abstract: Impulsivity is a personality trait exhibited by healthy individuals, but excessive impulsivity is associated with some mental disorders. Lesion and functional neuroimaging studies indicate that the ventromedial prefrontal region (VMPFC), including the orbitofrontal cortex (OFC), anterior cingulate cortex (ACC) and medial prefrontal cortex, and the amygdala may modulate impulsivity and aggression. However, no morphometric study has examined the association between VMPFC and impulsivity. We hypothesized that hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
200
7
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(242 citation statements)
references
References 60 publications
31
200
7
4
Order By: Relevance
“…Our observation seems to complement previous reports (Matsuo et al 2009) where instead at the level of the lateral part of the OFC a negative correlation was observed between GM and BIS measured impulsivity. This is not surprising given that it is well known that the medial and lateral OFC have distinct neuro-anatomical connections (Ferry et al 2000;Kondo et al 2003Kondo et al , 2005 and functional roles (Noonan et al 2010;Mar et al 2011;Bechara 2005).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our observation seems to complement previous reports (Matsuo et al 2009) where instead at the level of the lateral part of the OFC a negative correlation was observed between GM and BIS measured impulsivity. This is not surprising given that it is well known that the medial and lateral OFC have distinct neuro-anatomical connections (Ferry et al 2000;Kondo et al 2003Kondo et al , 2005 and functional roles (Noonan et al 2010;Mar et al 2011;Bechara 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, it seems reasonable to think that the positive relationship between GM volume and impulsivity in the MePFC/medial OFC may be the result of the engagement of reflective system (Bechara 2005) during decision making in subjects with higher impulsivity. Previous studies showed GM volume correlation in the OFC with motor impulsivity (Matsuo et al 2009). The lack of a similar correlation in our study may be due to the functional differences described above between the lateral and medial OFC and the fact that the latter region may be less sensitive to motor-related impulsivity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In our study, METH users with greater duration of METH use had smaller left caudal middle frontal volumes, suggesting that longer METH exposure may be more damaging in this region of the cortex. A study of healthy individuals found that smaller gray matter volume in the left and right orbitofrontal cortex and anterior cingulate cortex correlated with higher impulsivity, measured with the BIS (Matsuo et al, 2009). In our study, the caudal middle frontal volume was smaller in the METH users compared to the CON, which is consistent with others who similarly found smaller frontal gray matter volumes in METH users (Morales et al, 2012;Nakama et al, 2011).…”
Section: Thinner Frontal Cortices In Meth Usersmentioning
confidence: 99%
“…Impulsivity, measured with a delay-discounting task, correlated positively with gray matter density in the posterior cingulate cortex and ventral striatum and negatively with that in the left superior frontal gyrus (Schwartz et al, 2010). In non-drug using CON, gray matter volumes of the left OFC, right OFC, and left anterior cingulate cortex (ACC) correlated inversely with BIS total scores, and the left OFC volume also correlated inversely with motor impulsivity (Matsuo et al, 2009). These results suggest that smaller brain structures, perhaps due to effects of drugs, may account for more impulsive behavior observed.…”
Section: Introductionmentioning
confidence: 99%